CONTRASTIVE AND ERROR ANALYSIS OF INDONESIAN INFLUENCE ON ENGLISH ACADEMIC WRITING - Dalimunthe, Herika; Loudya Putri Utama; Dinda Sundana; Hasibuan, Shafira Hasan; Siti Ismahani (Linguistics and Literature Journal, 2025)
This study investigates the influence of the Indonesian language on English academic writing among Indonesian university students by integrating contrastive and error analysis approaches. Data were collected from 30 student essays and analyzed to identify grammatical, lexical, and rhetorical errors caused by first language (L1) interference. The results revealed that grammatical and syntactic errors were most frequent, including tense misuse, omission of plural markers, and article errors, followed by lexical transfer through literal translation and discourse-level issues such as indirect argumentation and poor coherence. These patterns reflect the structural and rhetorical contrasts between Indonesian and English. The findings suggest that students’ writing difficulties are rooted in both linguistic and cultural transfer, emphasizing the need for contrastive-based instruction and genre-oriented writing pedagogy. By understanding how Indonesian linguistic features shape English writing performance, educators can design more effective strategies to enhance students’ academic literacy and cross-linguistic awareness.Keywords: academic writing, contrastive analysis, error analysis, Indonesian interference